Sistem Informasi Geografis Lokasi Dan Rute Objek Wisata Kabupaten Tapanuli Tengah Menggunakan Metode Dijkstra - Sibuea, Grase Latifah; Suendri, Suendri (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
Geographic Information Systems (GIS) are systems that integrate geographic data with non-geographic data, allowing users to visualize, analyze and interpret spatial information more efficiently. This research aims to design and implement a Geographic Information System (GIS) that is effective and easy to use to map the location of tourist attractions and determine the shortest route to these destinations in Central Tapanuli Regency using the Dijkstra algorithm. This GIS allows tourists to visualize, analyze and access spatial information related to tourist locations and get recommendations for the best routes based on distance, travel time and road conditions. This system consists of an admin interface to manage tourist attraction data, nodes, and path graphs, as well as a user interface to view tourist lists, galleries, and search for nearby routes. The implementation of GIS and the Dijkstra algorithm is expected to improve the tourist experience, facilitate travel planning, and increase accessibility to tourist destinations in Central Tapanuli Regency, so that tourism potential in the area can be optimized and encourage regional economic growth.